COMERCIALIZAÇÃO DE FRANGOS E SEUS DERIVADOS NO MUNICÍPIO DE IJUÍ - Titzmann, Aline K.; Berto, Jorge L.; Quadros, Valmir J. d.; Garcia, Dagmar C.; Fernandes, Sandra B. V.; Uhde, Leonir T.; Junior, Ortiz S. (Salão do Conhecimento, 2013)
Resumo